Significance of corneal arcus - K Mohan Raj; P Arun Subhash Reddy; Vikram Chella Kumar (Wolters Kluwer Medknow Publications, 2015)
The corneal arcus consists of cholesterol, phospholipids and triglycerides. As serum triglyceride is one of the accurate of lipid metabolic state, greater importance was given, and it was found to be elevated in 72% of patients and a positive correlation with increasing age. This suggests a strong correlation between impairment of lipid metabolism and incidence of corneal arcus.